Understanding Emotion Regulation Strategies Among Youths: A Qualitative Study - Chang, Sherilyn; Vaingankar, Janhavi Ajit; Seow, Esmond; Samari, Ellaisha; Chua, Yi Chian; Luo, Nan; Verma, Swapna; Subramaniam, Mythily (Journal of adolescent research, 2025)
The period of youth encompasses a myriad of experiences that often elicit a range of emotions from the individual. This study was conducted to understand emotion regulation (ER) among youths, specifically to identify strategies employed by youths to regulate emotions, and to understand the perceived importance and impact of ER. Qualitative data were collected through one-to-one semi-structured interviews (n = 25) and focus group discussions (n = 11; total 70 participants) among youths aged between 15 and 24 years. Interviews were transcribed verbatim and inductive thematic analysis was used to analyze the data. ER strategies engaged by youths in this study were classified into the following themes: (1) developing emotional awareness and acceptance, (2) emotional catharsis, (3) calling for a timeout, and (4) positive thinking and reframing. Youths perceived the importance of regulating emotions as (1) ER contributes to rational thinking and decision-making, (2) poor ER worsens mental wellbeing, (3) ER provides stability in life, and has (4) relevance to current life stage and environment. Findings from this study illustrate the essential role of ER for youth’s healthy functioning and demonstrate the value of strengthening emotional regulatory capacities in them.